Wireless controller area networking using token frame scheme - Ng, Wei Lun (2012)
Traditional network employ address-centric approach in transmitting messages in a network. The approach is done by assigning each network interface that is connected to the network with an IP (internet protocol) address; given either by manual configuration or a dynamic mechanism such as DHCP (dynamic host configuration protocol). On the other hand, data-centric approach protocol such as sensor and control network that allows all routing nodes to look into the data content and perform aggregation on multiple input packets. Researches have proved that the datacentric approach has the advantage over address centric approach in a large scale network. In this thesis, a new wireless MAC protocol referred to as wireless controller area network (WCAN) is introduced. WCAN is an adaptation of its wired cousin,controller area network (CAN) protocol which follows the data-centric approach. However, yet, WCAN has not been properly defined and several researches have been proposed. Unfortunately, these approaches do not consider the network scalability issue of WCAN. Hence, a new WCAN protocol that utilizes token frame method has been proposed in this thesis. The proposed WCAN uses token frame method in providing channel access to nodes in the system. The token frame method follows the example used in wireless token ring protocol (WTRP) by Ergen et al; a MAC protocol for wireless networks that has efficiency in reducing the number of retransmission due to collisions. This method allows nodes to share a common broadcast channel by taking turns in transmitting upon receiving the token frame that are circulating around the network for a specified amount of time. The token frame allows nodes to access the network one at a time,giving „fair‟ chance to all nodes instead of competing against one another. Moreover, the token frame method provides high throughput in a bounded latency environment. The proposed method was built using QualNet platform to validate its algorithm. From the obtained results, it is shown that WCAN outperforms IEEE 802.11 by 62.5% in terms of throughput with increasing network size. Additionally, at a higher data interval rate, WCAN shows an improvement of 6% compared to IEEE 802.11.